The impact of word of mouth on consumer purchase intention for smartphone / Tuan Farah Azlinda Tuan Ismail - Tuan Ismail, Tuan Farah Azlinda (Faculty of Business and Management, 2020)
The purpose of this study is to determine the impact of WOM towards purchase intention for smartphone among youth generations. The research is based on a sample of 135 respondents. The result show that source attractiveness variables have significant influence on purchase intention for smartphone among youth generations. It involves the process of conducting the research such as in determining the sample, the reliability and validity of questionnaire and including the research design, sampling technique, data collection method also involving primary data, secondary source and data analysis technique. Word of mouth or known as WOM is defined as a new marketing tool in the hands of marketers emerging in the digital age that can be effectively leveraged to achieve the desired consumer groups and influence consumer attitudes effectively and it could generate a large amount of revenue. The main objective of this study is to determine whether the factors (ie: source credibility, source expertise, source attractiveness and social tie strength) have impact on consumer purchase intention for smartphone. The strongest relationship can be identified is between source attractiveness and purchase intention among youth generations.